AGROWISATA KOPI DI KLEDUNG KABUPATEN TEMANGGUNG DENGAN PENDEKATAN ARSITEKTUR EKOLOGI - Karlina Hangesti Rahayu; Rachmadi Nugroho; Ana Hardiana (ARSITEKTURA, 2016)
Temanggung Regency is a regency in Central Java Province. Existing issues in the Temanggung Regency becoming the background of planning and designing Coffee Agrotourism in Kledung Temanggung Regency based on Ecology Architecture, as for instances, the needs of new tourist destinations in the Temanggung Regency, the government's plan to develop new tourist destinations such as agrotourism area, the potential for coffee plants in Kledung, the principle of agrotourism stressed as low negative impact on nature and provides lessons to tourist about the importance of conservation and Kledung region as a region which provides protection underneath and protected areas that need to be preserved geology. The problem of the design is implement the concept of ecology with a focus on energy efficiency, minimazing cut and fill and waste management in the region and building Coffee Agrotourism in an effort to preserve nature. The purpose of this design is to get the design and building of Coffee Agrotourism region as a place of education and recreation on coffee plants by implementing the concept of Ecology Architecture. The method used is is a method of designing architecture based on Ecology Architecture approach. The results obtained Coffee Agrotourism based on Ecology Architecture approach that is applied to energy efficiency, minimazing cut and fill, and waste management. Keywords: Coffee Agrotourism, Ecology Architecture, Energy Efficiency, Cut and fill, Waste Management.